2014
DOI: 10.1093/mp/ssu106
|View full text |Cite
|
Sign up to set email alerts
|

SPINDLY, ERECTA, and Its Ligand STOMAGEN Have a Role in Redox-Mediated Cortex Proliferation in the Arabidopsis Root

Abstract: SUMMARYReactive oxygen species (ROS) are signaling molecules, but how they are perceived in plants remains unclear. This study showed that cortex proliferation in the Arabidopsis root can be induced by hydrogen peroxide and that the receptor kinase ERECTA and one of its ligands, STOMAGEN, are involved in a signaling pathway that couples ROS sensing with redox-mediated cortex proliferation. This study also revealed a new role for SPINDLY (SPY), a putative O-GlcNAc transferase, in cellular redox homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 65 publications
3
62
0
Order By: Relevance
“…The asterisks indicate statistically significant differences (***p<0.001; **p<0.01) Brackets represent standard errors over twenty replications (ten biological replicates, each with two pools of independent samples) for pGA20 and pPHOR, and two replications (i.e., two pools of samples) for wild-type control believed due to its additional roles in cytokinin and redox signaling, and consequent effects on plant root development, brassinosteroid synthesis, circadian rhythm and photoperiodic flowering, and abiotic stress response (Tseng et al 2004;Swain et al 2001;Shimada et al 2006;Filardo et al 2009;Qin et al 2011;Steiner et al 2012;Cui et al 2014). Studies of biomass allocation showed that the increase in biomass growth we observed was associated with preferential allocation to shoots.…”
Section: Discussionmentioning
confidence: 99%
“…The asterisks indicate statistically significant differences (***p<0.001; **p<0.01) Brackets represent standard errors over twenty replications (ten biological replicates, each with two pools of independent samples) for pGA20 and pPHOR, and two replications (i.e., two pools of samples) for wild-type control believed due to its additional roles in cytokinin and redox signaling, and consequent effects on plant root development, brassinosteroid synthesis, circadian rhythm and photoperiodic flowering, and abiotic stress response (Tseng et al 2004;Swain et al 2001;Shimada et al 2006;Filardo et al 2009;Qin et al 2011;Steiner et al 2012;Cui et al 2014). Studies of biomass allocation showed that the increase in biomass growth we observed was associated with preferential allocation to shoots.…”
Section: Discussionmentioning
confidence: 99%
“…3 To determine how SPY affects root development, we conducted transcript profiling with roots from spy-3 mutant and wild type plants. 2 This transcriptome analysis showed that genes involved in redox homeostasis are enriched among the genes whose expression is altered in the spy mutant. Consistent with this, we found that the spy mutant has an elevated level of reactive oxygen species (ROS).…”
mentioning
confidence: 97%
“…Our recent studies suggest that root cortex proliferation is a protective mechanism against abiotic stress. 2 The initial evidence suggesting this role for root cortex is derived from our studies of the spy mutant. In the root of oneweek-old wild-type seedlings of Arabidopsis thaliana, there is a single layer of cortex; in contrast, in the spy mutant, an additional layer of cortex is produced from the endodermis within 3 days of germination.…”
mentioning
confidence: 99%
See 2 more Smart Citations